1996
DOI: 10.1111/j.1440-1746.1996.tb00016.x
|View full text |Cite
|
Sign up to set email alerts
|

Sulindac and indomethacin inhibit formation of aberrant crypt foci in the colons of dimethyl hydrazine treated rats

Abstract: Aberrant crypt foci are microscopic lesions found in the colons of rodents treated with carcinogens, and in patients with premalignant colorectal conditions. They consist of single or multiple abnormal crypts and show cellular changes ranging from dysplasia to microscopic adenomacarcinoma. It is thought that these lesions represent the initial stages of the adenomacarcinoma path that results in the development of colorectal neoplasia. We have examined the effect of sulindac and indomethacin on the formation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 13 publications
1
13
0
Order By: Relevance
“…34 A number of reports studying the potential chemopreventative effect of non-steroidal anti-inflammatory agents have described a reduction in aberrant crypt foci and subsequent tumour formation. 35,36 Our study clearly demonstrates that glycine-extended gastrin 17 increases the number of aberrant crypt foci formed in the colorectal mucosa of rats after treatment with azoxymethane in a pattern consistent with its action as a proliferative agent in the colonic mucosa. Glycine-extended gastrin 17 could thus potentially act as a promoter of carcinogenesis, but definitive evidence for this proposal would require a long term study to establish that tumors occur either earlier, or more abundantly, or both, in rats treated with glycine-extended gastrin 17 compared to controls.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…34 A number of reports studying the potential chemopreventative effect of non-steroidal anti-inflammatory agents have described a reduction in aberrant crypt foci and subsequent tumour formation. 35,36 Our study clearly demonstrates that glycine-extended gastrin 17 increases the number of aberrant crypt foci formed in the colorectal mucosa of rats after treatment with azoxymethane in a pattern consistent with its action as a proliferative agent in the colonic mucosa. Glycine-extended gastrin 17 could thus potentially act as a promoter of carcinogenesis, but definitive evidence for this proposal would require a long term study to establish that tumors occur either earlier, or more abundantly, or both, in rats treated with glycine-extended gastrin 17 compared to controls.…”
Section: Discussionsupporting
confidence: 67%
“…Previous work on the ACF model suggests that in general increases in ACF number are associated with a subsequent increase in tumour frequency. 32,35,36 In the case of transgenic mice overexpressing progastrin the increase in number of aberrant crypt foci after treatment with azoxymethane compared to wildtype controls 9 is ultimately followed by the development of greater numbers of larger adenomas and adenocarcinomas of the colon. 30 The implications of these findings for human disease are still to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…ACFs are considered to be an early preneoplastic lesion in the colon (75), and the ability to decrease the frequency of ACF after carcinogen treatment is used routinely in experimental models of colon cancer to estimate the cancer preventive effect of different agents (76). It is particularly well established that NSAIDs (77)(78)(79) and celecoxib (80)(81)(82)(83) decrease the frequency of carcinogen-induced ACFs in the colon in animal models. It has also been shown that the number of ACF in patients who received sulindac sulfide is decreased (84).…”
Section: Discussionmentioning
confidence: 99%
“…Reduction of COX enzyme activity by NSAIDs suppresses intestinal carcinogenesis in Apc Min/+ mice (24)(25)(26) as well as other models of intestinal cancer (7,(27)(28)(29)(30). Expression of polyamine biosynthetic enzyme, ornithine decarboxylase (ODC), is elevated in the intestinal tissues of Apc Min/+ mice and in apparently normal colonicmucosal biopsies from FAP patients (31,32).…”
Section: Introductionmentioning
confidence: 99%